The role of Learning Motivation (Extrinsic and Intrinsic) and its Implications in the Learning Process - Tysa Sufia Rahmi; Neviyarni S (Postgraduate School, Universitas Negeri Padang, 2022)
Learning is a process that is conducted so that the changes of behavior, learning is an important process of educational activities at school, a good education is education that is able to deliver students in achieving the goals of education. One of the things that influence the achievement of educational goals is learning motivation, motivation is one of the factors that will support students in following the learning process, the motivation will determine the level of activities and behavior of students in achieving learning goals. Judging from the source, motivation is divided into two, namely extrinsic and intrinsic motivation, extrinsic motivation is an impulse that originates from outside the individual to be able to master a competence to solve a problem. While intrinsic motivation is a strong encouragement sourced from within someone, the greater the motivation or encouragement that comes from within a person, the higher the ability to master a competence.